2021
DOI: 10.3390/rs13163246
|View full text |Cite
|
Sign up to set email alerts
|

Validation of FY-3D MERSI-2 Precipitable Water Vapor (PWV) Datasets Using Ground-Based PWV Data from AERONET

Abstract: The medium resolution spectral imager-2 (MERSI-2) is one of the most important sensors onboard China’s latest polar-orbiting meteorological satellite, Fengyun-3D (FY-3D). The National Satellite Meteorological Center of China Meteorological Administration has developed four precipitable water vapor (PWV) datasets using five near-infrared bands of MERSI-2, including the P905 dataset, P936 dataset, P940 dataset and the fusion dataset of the above three datasets. For the convenience of users, we comprehensively ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 51 publications
0
0
0
Order By: Relevance
“…The Aerosol Robotic Network, a global ground-based aerosol observation network equipped with many sun photometers, has been widely used and validated worldwide. Xie et al [48] used ground-based WVC data from 369 Aerosol Robotic Network sites to validate the MERSI-2 WVC products. The results showed that all four MERSI-2 WVC datasets (WVC c , WVC 905 , WVC 936 , and WVC 940 ) were better than the MODIS WVC dataset due to the serious overestimation found in the MODIS WVC data.…”
Section: Errors From the Fy-3d Wvcmentioning
confidence: 99%
“…The Aerosol Robotic Network, a global ground-based aerosol observation network equipped with many sun photometers, has been widely used and validated worldwide. Xie et al [48] used ground-based WVC data from 369 Aerosol Robotic Network sites to validate the MERSI-2 WVC products. The results showed that all four MERSI-2 WVC datasets (WVC c , WVC 905 , WVC 936 , and WVC 940 ) were better than the MODIS WVC dataset due to the serious overestimation found in the MODIS WVC data.…”
Section: Errors From the Fy-3d Wvcmentioning
confidence: 99%